(untitled) (Research, Society and Development, 2020)
Climatic conditions affect the productivity and economic viability of agriculture that is challenged by constant temperature and precipitation variations through the time. This study aimed to estimate climate change in the Guarapuava microregion in the state of Paraná, analyzing the impacts on corn crop, using modeling for future scenarios and comparing it with a base scenario of the past. Mathematical adequacy models were fitted using Multiple Criteria Analysis (MCA) and Analytical Hierarchy Process (AHP), using the climatic scenarios RCP4.5 and RCP8.5 (IPCC) for the calculation of the Land suitability potential of the crops considering the variables soil, topography and climate. It was concluded thatthe projection of average temperature increase during the crop cycle, is the environmental factor of greatest impact for the reduction of the agricultural aptitude index for corn in Guarapuava microregion, in the year 2050.